Artificial Intelligence Regulation in the Protection of Democracy: A Legal Analysis of Political Deepfakes and Disinformation in the 2024 Election - Andi Nur Azizah Ardan Paliwang; Ni Luh Putu Erika Swandiani (Fakultas Hukum, Universitas Sains dan Teknologi Komputer, 2025)
The advent of Artificial Intelligence (AI) poses new hurdles to democracy, especially in the form of political deepfakes and disinformation during Indonesia's 2024 general elections. This study evaluates the effectiveness of national legal regulations on AI-generated manipulative content and aims to identify legal gaps that undermine the state's democratic integrity. Using a case-study qualitative approach and a normative legal method, data were collected from regulatory studies, examination of deepfake cases, and interviews with experts. Findings show that there are no specific laws or regulations governing political deepfakes: of the four cases analyzed, only one has been acted on by regulatory authorities. Such findings imply a weak legal defence against digital manipulation and further erode public trust in the electoral process. The study's major contribution is the development of a new adaptive regulatory framework that advocates integrating law and technology to ensure the integrity of democracy. The research builds on the literature on digital law. It provides concrete policy recommendations to enhance regulatory mechanisms and institutional capacity to stamp out efforts to address AI-induced disinformation threats. Beyond theoretical contribution, this study offers practical policy guidance for lawmakers, electoral regulators, and civil society in designing adaptive legal frameworks that safeguard democratic integrity amid the growing risks of AI-driven manipulation